Ketentuan Regulasi Mengenai Perdagangan Orang terhadap Pekerja Migran Digital - Buyung Pamungkas Shakti; Frans Simangunsong (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid development of digital technology has created a new form of human trafficking through the recruitment of digital migrant workers via social media and online platforms. This phenomenon presents legal challenges because exploitation no longer necessarily involves the physical movement of victims but is carried out through technological control and digital coercion. This study aims to analyze the adequacy of Indonesia’s legal framework, identify law enforcement challenges, and examine the need for harmonization with international legal instruments in addressing digital human trafficking. The research employs a normative legal method using statutory and conceptual approaches. The findings indicate that existing regulations provide a legal basis but do not explicitly regulate digital human trafficking. Law enforcement remains constrained by limited technological capacity, low digital literacy, weak inter-agency coordination, and cross-border jurisdictional complexities. Therefore, legal reform and regulatory harmonization are necessary to strengthen the protection of digital migrant workers and improve the effectiveness of combating human trafficking in the digital era.